ORAL MANIFESTATIONS OF HEPATITIS C VIRUS - Vladimir E. Panov (Peytchinski Publishing, 2013)
Hepatitis C virus (HCV) infection is a serious public health problem. New infections continue to occur, and morbidity and mortality are increasing. The date reported that 3% of infected world population are affected.Morbidity associated with hepatitis C virus infection can involve a variety of extrahepatic conditions including the oral region. Some of the oral manifestation are oral disease like lichen planus and Sjögren-like sialadenitis , other affects the dental status, and side effect of the virus therapy. The aim of this review is to summarize the oral sings, accompanying hepatitis C virus.